Sejarah Perkembangan Televisi dan Perannya sebagai Media Dakwah Islam - Hany Tasya Luthfiah; Erwan Effendy; Agus Kurniawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
At first Da'wah only used traditional media, which later developed using modern technology, one of which was television. Television as a communication medium can be an attractive channel for conveying good messages to the public, besides that television is also close to everyday life. Basically, using technology as a medium of da'wah will help the goals of da'wah be conveyed quickly. This research uses a qualitative approach using descriptive methods. The collection of data used in this study is observation. Observations are made to form a picture of events or the reality of events in order to answer research. Television was first introduced in Indonesia in 1962 and after independence, Indonesia started building intelligence agencies to promote sustainable development. Television was born and developed in Indonesia along with the birth of many communication scientists, so that academic research on television was born. The use of television media in preaching can stimulate the human senses and attract attention. The more precise and effective the wasilah is used, the more effective the effort to understand Islamic teachings will be. In general, the advantage of teevision as a medium of propaganda is that it is very persuasive because the audience can see images and sound directly at the same time. That way television is also very fast, modern, and very convincing. However, even though the advantages of television are very prominent, television is not always the best medium for preaching. Like other media, television also has some weaknesses. Keywords: Television, Media, Da’wah